2016
DOI: 10.1371/journal.pone.0168389
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Transcription Factor HSF1 Induces Ovarian Cancer Epithelial-Mesenchymal Transition in a 3D Spheroid Growth Model

Abstract: Ovarian cancer is the most lethal gynecological cancer, with over 200,000 women diagnosed each year and over half of those cases leading to death. The proteotoxic stress-responsive transcription factor HSF1 is frequently overexpressed in a variety of cancers and is vital to cellular proliferation and invasion in some cancers. Upon analysis of various patient data sets, we find that HSF1 is frequently overexpressed in ovarian tumor samples. In order to determine the role of HSF1 in ovarian cancer, inducible HSF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 32 publications
2
34
0
Order By: Relevance
“…This study revealed that HSF1 is a direct target gene of YY1, which induces HSF1 gene transcription. 45,46 Interestingly, although YY1-HSF1 pathway plays an important F I G U R E 8 FAM3C-YY1-HSF1 axis was activated in human breast cancer tissues. For the first time, our findings revealed that these important molecules are coordinated to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study revealed that HSF1 is a direct target gene of YY1, which induces HSF1 gene transcription. 45,46 Interestingly, although YY1-HSF1 pathway plays an important F I G U R E 8 FAM3C-YY1-HSF1 axis was activated in human breast cancer tissues. For the first time, our findings revealed that these important molecules are coordinated to promote the proliferation and migration of breast cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…New FAM3C-YY1 pathway also provides an explanation for the findings that TGFβ induces HSF1 expression with unclear mechanism in ovarian and breast cancer cells. 45,46 Interestingly, although YY1-HSF1 pathway plays an important F I G U R E 8 FAM3C-YY1-HSF1 axis was activated in human breast cancer tissues. (A-C) Immunohistochemical staining revealed that FAM3C (A), YY1 (B) and HSF1 (C) protein levels were increased in breast cancer tissues when compared normal breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, it was demonstrated that HSF1 promotes TGFβ-induced EMT, tumorigenesis, and metastases in a murine breast cancer model [161]; the EMT-promoting mechanism was due to HSF1-mediated stimulation of the RAS/RAF/MEK/ERK1/2 signaling pathway. Additionally, HSF1 was found to be required for EMT in ovarian cancer (including a spheroid growth model) [162], hepatocellular carcinoma [163], and pancreatic cancer [164]. In the latter case, the abnormal HSF1 activation (phosphorylation) resulting in EMT induction in pancreatic cancer cells was correlated with the failure of AMPK activation in pancreatic tumors [164].…”
Section: Hsf1 and Hsf1-activating Exposurementioning
confidence: 99%
“…Upon activation by a variety of stimuli such as heat shock, infection and heavy metal toxicity, HSF1 forms trimers, translocates into the nucleus and induces various heat shock proteins (HSPs) by binding to heat shock elements (HSEs) on HSP promoters (4,5). Accumulating evidence has suggested that HSF1 is a powerful modifier of carcinogenesis; HSF1 levels are elevated in several cancers, including breast (6), ovarian (7) and cervical cancer (8). Activated or elevated HSF1 is often associated with resistance to chemotherapy drugs or poor prognosis (9).…”
Section: Introductionmentioning
confidence: 99%